Women in Translational Medicine: Tools to Break the Glass Ceiling - Bots, Sophie H.; Zuidgeest, Mira G. P.; Gohar, Aisha; Eikendal, Anouk L. M.; Petrelli, Alessandra; van Os-Medendorp, Harmieke; van der Schaaf, Marieke F.; van Sorge, Nina M.; van Wijk, Myriam; Middendorp, Sabine; Speksnijder, Caroline M.; Klipstein-Grobusch, Kerstin; et al. (Frontiers in Medicine, 2018)
not applicable